Interactions between Neisseria meningitidis and human cells that promote colonisation and disease. - Corbett, A; Exley, R; Bourdoulous, S; Tang, C (2004)
Neisseria meningitidis is the leading cause of bacterial meningitis, a potentially fatal condition that particularly affects children. Multiple steps are involved during the pathogenesis of infection, including the colonisation of healthy individuals and invasion of the bacterium into the cerebrospinal fluid. The bacterium is capable of adhering to, and entering into, a range of human cell types, which facilitates its ability to cause disease. This article summarises the molecular basis of host-pathogen interactions at the cellular level during meningococcal carriage and disease.